Hybrid nanocomposites based on CeO2, AgNANO and cellulose: preparation, characterization and antimicrobial study - Machado, Gustavo Teixeira; Meireles, Carla da Silva; Andrade, George Ricardo Santana (Brazilian Journal of Production Engineering, 2023)
Wound healing is the focus of numerous studies in the literature, since the exposure of wounds or lesions to the skin makes the body susceptible to biological attacks, such as bacteria and fungi, directly affecting the quality of life and health systems in different spheres. In this context, the search for innovative strategies for the treatment of skin wounds has been intensified, with a main focus on the use of biomaterials. The use of cellulose as a polymeric matrix, incorporating cerium oxide (CeO2) and silver nanoparticles (AgNANO), offers the biodressing healing properties, such as antioxidant and antibacterial activity, respectively. Studies conducted using techniques such as UV-vis and XRD revealed that the bandgap energy of CeO2 nanoparticles is approximately 2.98 eV, with a fluorite-type crystallite geometry of cubic symmetry and an average diameter of 6.64 nm. The lignin amount was 3.1%. Discs prepared from pure cellulose and membranes impregnated with CeO2/AgNANO NPs demonstrated antimicrobial activity against bacteria such as S. aureus and E. coli.